2022
DOI: 10.3390/ijms232315054
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol: Antimicrobial Properties, Sources, Clinical, and Traditional Applications

Abstract: Flavonoids are a category of plant-derived compounds which exhibit a large number of health-related effects. One of the most well-known and studied flavonoids is kaempferol, which can be found in a wide variety of herbs and plant families. Apart from their anticarcinogenic and anti-inflammatory effects, kaempferol and its associated compounds also exhibit antibacterial, antifungal, and antiprotozoal activities. The development of drugs and treatment schemes based on these compounds is becoming increasingly imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(54 citation statements)
references
References 431 publications
0
54
0
Order By: Relevance
“…The structure of flavonoids plays an important role in anti-inflammatory activity. For example Betulaceae , Fabaceae , Asteraceae and Apiaceae families are rich in quercetin, which extincts free radicals formed during cellular metabolism [ 36 ]; Asphodelaceae and Scrophulariaceae families contain luteolin, which presents anticancer properties and is associated with the induction of apoptosis and inhibition of cell proliferation, metastasis and angiogenesis [ 37 ], while the Fabaceae family is abundant in kaempferol, isoflavones and flavanols, which are known to act as antioxidants and anticancer and anti-inflammatory agents in various contexts [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The structure of flavonoids plays an important role in anti-inflammatory activity. For example Betulaceae , Fabaceae , Asteraceae and Apiaceae families are rich in quercetin, which extincts free radicals formed during cellular metabolism [ 36 ]; Asphodelaceae and Scrophulariaceae families contain luteolin, which presents anticancer properties and is associated with the induction of apoptosis and inhibition of cell proliferation, metastasis and angiogenesis [ 37 ], while the Fabaceae family is abundant in kaempferol, isoflavones and flavanols, which are known to act as antioxidants and anticancer and anti-inflammatory agents in various contexts [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the intake of KMF-rich nutraceuticals is also common in the geriatric population who suffer from various age-related ailments such as cardiovascular diseases, diabetes, and cancers. In spite of the growing market demand for KMF in foods and beverages, this small molecule is usually derived from plants, which limits its application in the food industry due to the high production cost (Periferakis et al, 2022).…”
Section: The Optimum Reaction Timementioning
confidence: 99%
“…Kaempferol, as a natural flavonoid, exhibits a host of antivirulence activities (Periferakis et al, 2022). A current study suggested that kaempferol acted as a promising candidate drug against S. pneumoniae by inhibiting the pore formation activity of pneumolysin functioning through binding with catalytic active sites, and consequently reducing the pneumolysin‐mediated hemolytic activity.…”
Section: Preclinical Studies Of Plant‐derived Antivirulence Agents As...mentioning
confidence: 99%